Neural regulation of the thymus: past, current, and future perspectives - Carpenter, Randall S.; Lagou, Maria K.; Karagiannis, George S.; Maryanovich, Maria (Frontiers in Immunology, 2025)
The thymus is a primary lymphoid organ critical for the development of mature T cells from hematopoietic progenitors. A highly structured organ, the thymus contains distinct regions, precise cytoarchitecture, and molecular signals tightly regulating thymopoiesis. Although the above are well-understood, the structural and functional implications of thymic innervation are largely neglected. In general, neural regulation has become increasingly identified as a critical component of immune cell development and function. The central nervous system (CNS) in the brain coordinates these immunological responses both by direct innervation through peripheral nerves and by neuroendocrine signaling. Yet how these signals, particularly direct neural innervation, may regulate the thymus biology is unclear and understudied. In this review, we highlight historical and current data demonstrating direct neural input to the thymus and assess current evidence of the neural regulation of thymopoiesis. We further discuss the current knowledge gaps and summarize recent advances in techniques that could be used to study how nerves regulate the thymic microenvironment.